EFFECTS OF STRATIGIC MARKETING ON BUSINESS PERFORMANCE OF SMALL BUSINESS IN BAKARA MARKET MOGADISHU SOMALIA - MOHAMUD, ALI YUSUF; gichinga, Dr Lucy (IJRDO - Journal of Business Management, 2016)
The purpose was to investigate the impact of small businesses on the Marketingstrategy on business Performance in Mogadishu -Somalia, by identifying and understanding thebest ways that small businesses can be successful. and to find out the role of small business inmarketing strategy on business Performance The general objective of the study is to investigate theeffects of strategic marketing on business performance the research question of this study waswhat assess the effects of market Segmentation on Business Performance How To assess the effectsof Cost Leadership on Business Performance .The Research Design a descriptive case studyapproach was use in order to determine and report about the effects of strategic marketing onbusiness performance of small business. The sample technique of this study was simple randomsampling. The questionnaire translates the research objective into specific questions targetpopulation of small business of Mogadishu Somalia. The questionnaire was 75 employees.Proportionate stratified random sampling technique was used for this study. The data collected inthis study was analyzed using descriptive statistics through SPSS version 16.0. There was a weakpositive but insignificant business Performance correlation market segmentation There was a weakpositive and significant business Performance correlation between cost leadership There was astrong negative and highly significant correlation between product differentiation and businessperformance There was a moderately positive and highly significant correlation between effects ofmarket strategy and business performance .